Nitrogen Cycling and Community Structure of Proteobacterial β-Subgroup Ammonia-Oxidizing Bacteria within Polluted Marine Fish Farm Sediments - McCaig, Allison E. (American Society for Microbiology, 1999)
A multidisciplinary approach was used to study the effects of pollution from a marine fish farm on nitrification rates and on the community structure of ammonia-oxidizing bacteria in the underlying sediment. Organic content, ammonium concentrations, nitrification rates, and ammonia oxidizer most-probable-number counts were determined in samples of sediment collected from beneath a fish cage and on a transect at 20 and 40 m from the cage. The data suggest that nitrogen cycling was significantly disrupted directly beneath the fish cage, with inhibition of nitrification and denitrification. Although visual examination indicated some slight changes in sediment appearance at 20 m, all other measurements were similar to those obtained at 40 m, where the sediment was considered pristine. The community structures of proteobacterial β-subgroup ammonia-oxidizing bacteria at the sampling sites were compared by PCR amplification of 16S ribosomal DNA (rDNA), using primers which target this group. PCR products were analyzed by denaturing gradient gel electrophoresis (DGGE) and with oligonucleotide hybridization probes specific for different ammonia oxidizers. A DGGE doublet observed in PCR products from the highly polluted fish cage sediment sample was present at a lower intensity in the 20-m sample but was absent from the pristine 40-m sample station. Band migration, hybridization, and sequencing demonstrated that the doublet corresponded to a marine Nitrosomonas group which was originally observed in 16S rDNA clone libraries prepared from the same sediment samples but with different PCR primers. Our data suggest that this novel Nitrosomonas subgroup was selected for within polluted fish farm sediments and that the relative abundance of this group was influenced by the extent of pollution.